2022
DOI: 10.1108/md-06-2022-0759
|View full text |Cite
|
Sign up to set email alerts
|

Environmental dynamism and sustainability: the mediating role of innovation, strategic flexibility and HR development

Abstract: PurposeThe purpose of this paper is to examine whether environmental dynamism can drive firms to adopt sustainability, taking into consideration the mediating role of the innovation process, strategic flexibility and human resource development in this relationship.Design/methodology/approachThe proposed framework is tested by confirmatory factor analysis and finally structural equation modeling (SEM) using the survey data from 513 Greek firms.FindingsThe results show that environmental dynamism drives firms to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 99 publications
0
8
0
Order By: Relevance
“…Based on this conceptualization of sustainability, we further expanded the definition and value of sustainability in the HRD setting. Our analysis revealed that “sustainability” was the most frequently used term in 13 out of the 59 publications, without any other words added (Bianchi et al, 2022; Brandi & Thomassen, 2021; Dragan et al, 2021; Garbie, 2015; Kafetzopoulos, 2023; Kolk, 2016; Maltseva et al, 2019; Palthe, 2013; Sheehan et al, 2014; Valentin, 2015; Vodonick, 2018; Waite, 2013).…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations
“…Based on this conceptualization of sustainability, we further expanded the definition and value of sustainability in the HRD setting. Our analysis revealed that “sustainability” was the most frequently used term in 13 out of the 59 publications, without any other words added (Bianchi et al, 2022; Brandi & Thomassen, 2021; Dragan et al, 2021; Garbie, 2015; Kafetzopoulos, 2023; Kolk, 2016; Maltseva et al, 2019; Palthe, 2013; Sheehan et al, 2014; Valentin, 2015; Vodonick, 2018; Waite, 2013).…”
Section: Resultsmentioning
confidence: 93%
“…Nations: Poland and Denmark (Zgrzywa-Ziemak & Walecka-Jankowska, 2021), United States (Craig & Allen, 2013; Eccles et al, 2014), Turkey (Cop et al, 2020; Özgül & Zehir, 2023), Greek (Kafetzopoulos, 2023), Canada (Vito et al, 2023), German (Wicki & Hansen, 2019), United Kingdom (Ipiranga & Aguiar, 2014), China (Abbas et al, 2022), Taiwan (Chan et al, 2022), Srilanka (Wijethilake & Upadhaya, 2020), Rome (Dragan et al, 2021), Brazil (Figueiredo et al, 2021), and Malaysia (Bilan et al, 2020; Yusoff et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Green practices fall within the environmental dimension of sustainability, a stream that has recently started exploring interactions with SF, but is still underexplored, thus leading to many fruitful avenues for future research (e.g. Kafetzopoulos, 2022; Nwachukwu and Vu, 2020). Research about sustainability has been gaining increasing importance due to the pressing need to pursue sustainability objectives set at the international level.…”
Section: Discussion and Avenues For Future Research On Sfmentioning
confidence: 99%